2021
DOI: 10.1002/jmd2.12199
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydrobiopterin deficiencies: Lesson from clinical experience

Abstract: Objectives The present study describes clinical, biochemical, molecular genetic data, current treatment strategies and follow‐up in nine patients with tetrahydrobiopterin (BH4) deficiency due to various inherited genetic defects. Methods We analyzed clinical, biochemical, and molecular data of nine patients with suspected BH4 deficiency. All patients were diagnosed at Ege University Faculty of Medicine in Izmir, Turkey and comprised data collected from 2006 to 2019. The diagnostic laboratory examinations inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
0
11
1
Order By: Relevance
“…The frequency of PCD deficiency in the present study was 7.1%, exceeding the 2.6% reported in BIODEFdb (BIODEFdb), which could suggest that the frequency of the different BH4 disorders varies among populations ( Souza et al, 2018 ; Carducci et al, 2020 ; Bozaci et al, 2021 ; Gundorova et al, 2021 ; Ray et al, 2022 ). We only found one homozygous c.289G > A or p.(Glu97Lys) male patient.…”
Section: Discussioncontrasting
confidence: 86%
“…The frequency of PCD deficiency in the present study was 7.1%, exceeding the 2.6% reported in BIODEFdb (BIODEFdb), which could suggest that the frequency of the different BH4 disorders varies among populations ( Souza et al, 2018 ; Carducci et al, 2020 ; Bozaci et al, 2021 ; Gundorova et al, 2021 ; Ray et al, 2022 ). We only found one homozygous c.289G > A or p.(Glu97Lys) male patient.…”
Section: Discussioncontrasting
confidence: 86%
“…Hyperkinesia and locomotor disorders have been reported with the prolonged use of the parent drug phenytoin, and further investigations are warranted to determine whether such effects may be due to the impairment of GTPCH1 activity by its metabolite phenytoin catechol. It is well reported that BH 4 deficient conditions, such as BH 4 -dependent congenital hyperphenylalaninemia and dopa-responsive dystonia, express phenotypes of variable severity, ranging from poor motor control, hypo/hypertonia to Parkinsonism [ 9 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…While GTPCH1 plays a well-documented role within the setting of both cardiovascular and neurological diseases [ 3 , 8 , 9 ], it has also garnered significant interest regarding the role that it may have in pain pathways [ 10 ]. In a hallmark study, the enzyme was identified as a key modulator in peripheral neuropathic and inflammatory pain settings [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early and correct treatment for patients affected by DHPR deficiency is essential, as a delay or an inadequate treatment may result in severe neurologic impairment including developmental delay/intellective disability (DD/ID), microcephaly, seizures, movement disorders, cerebral palsy, and other neurological impairments. Bozaci et al 12 reported on nine patients: three affected by DHPR deficiency and six by BH 4 deficiency. All the three patients affected by DHPR deficiency were females.…”
Section: Discussionmentioning
confidence: 99%
“…Long-acting dopamine agonists are also utilized in the treatment of this disorder. [11][12][13][14][15] We reported here a 12-year-old girl who was previously hospitalized for a few days to a local pediatric emergency section for two short episodes of seizures. One month after the discharged, she came to Pediatric Department of Catania University (Italy) presenting with episodes of vomiting, headache, irritability, acute confusional state, seizures, and left lower limb hypotonia; she was known to be affected by DHPR deficiency and in treatment since infancy.…”
Section: Introductionmentioning
confidence: 99%